3 A Political Ecology of the Medieval Castle. Issue 1 (2nd July 2018) - Johnson, Matthew
ABSTRACT: Recent work in castle studies has moved away from their military role, towards a stress on social life, aesthetics, symbolism, and "status." While this social‐cultural turn is a marked advance, it has not always been thought through in an anthropological or theorized way; nor have social‐cultural interpretations been related to everyday practices. Consequently, "social" analyses of castles have tended to be rather disembodied, and to be limited in their accounts of power and inequality. In this paper, I sketch out what a political ecology of the castle might look like, with reference to the late medieval castle of Bodiam in south‐east England. I focus on how the castle and its surrounding landscape work to control, delimit, and define flows—flows of things, of animals, and of people, circulating in and around the castle and its context. Flows work at a series of different scales ranging from the position and practices of the human body within castle spaces, to the local and regional, to the networks of religion and power across Europe and beyond. Things, animals, and people move within and around the castle hall and kitchens, upper and lower courtyards, the ancillary buildings of demesne farm, deerpark, fishponds and estate, the local, regional, and wider landscape and environment. Material flows help define the nature and scope of social relations; the description of such flows allows a clearer idea of the castle's role in materializing inequality to be delineated and understood.